Analysis of the Influence of Push, Pull and Mooring Effects on Switching Intention (Study on Participants of the National Health Insurance Program) - Teguh, Christanto; Salim, Lina (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study aims to analyze the effect of push, pull, and mooring effect on switching intention in the group of participants in the National Health Insurance (JKN) program in the South Jakarta area. The object of this study is a member of the JKN participants at the Atma Jaya Semanggi Clinic. Data was collected using non-probability sampling, especially purposive sampling, with 150 respondents. Empirical data were processed using the Structural Equation Modeling (SEM) method with SmartPLS. All five hypotheses were accepted. The analysis results showed that the push, pull, and mooring effects had a direct and significant effect on switching intention. The mooring effect moderates the push and pull effects on switching intention. The implications of the results of this study show that health facilities need to pay attention to the factors that drive dissatisfaction, increase the attractiveness of alternative services, and manage patient attachment strategically to retain JKN participants. Clinics also need to design loyalty programs and service innovations based on patient needs to strengthen long-term relationships. In addition, BPJS Kesehatan is expected to improve the FKTP selection mechanism through education and increased service quality transparency to reduce participants' intention to switch